Implementasi Program Intensifikasi Bahasa Arab Berbasis Peer Tutoring (Kajian Antropolinguistik) - Khabibul Khoiri; Yusuf Mustofa (Pusat riset dan Inovasi Nasional, 2025)
The purpose of this research is to reveal Arabic language learning through an Arabic language intensification program based on using the peer tutoring method. The problem in this study is that students in the Arabic language education study program at the Darul A'mal Islamic Institute of Lampung as Arabic language learners have uneven Arabic language competencies, this is due to different educational backgrounds including modern Islamic boarding schools, Salaf, and non-Islamic boarding schools. The method used in this study is field research supported by data collection techniques, namely observation, interviews, and documentation, all data obtained are studied using anthropolinguistic theory. The main data sources in the study are management, lecturers, and students. This study succeeded in revealing that the success of the implementation of the peer tutoring-based Arabic language intensification program is supported by implementing three aspects, namely performance, indexicality, and participation, where this concept emphasizes the implementation of active interaction between lecturers and students in the Arabic language learning process and practicing Arabic by involving socio-culture and native Arabic speakers in it. Then the factors that support the success of students in learning Arabic are having grammatical competence, communicative and pragmatic competence, as well as Arabic language skills, namely istima', kalam, qiro'ah, and kitabah.